Effects of Training Opportunities on Employees’ Career Development: A Mixed-Methods Study of Moshi Municipal Council, Tanzania - Prisca Fredrick Ntinda; Hezron Onyancha; Amembah A. Lamu Amos (Journal of Management and Entrepreneurship Research, 2026)
Objective: This study assessed the effects of training opportunities on employees’ career development in Moshi Municipal Council, Tanzania. Research Design & Methods: A convergent mixed-methods design was employed, combining quantitative and qualitative approaches. The target population comprised 325 employees across nine departments, from which a sample of 179 respondents was determined using Yamane’s (1967) formula. Simple random sampling was applied for employees, while purposive sampling targeted Heads of Departments. Data were collected through structured questionnaires and interview guides. Quantitative data were analyzed using SPSS version 22, employing descriptive statistics, while qualitative data were analyzed thematically and supported by direct quotations. Ethical principles of informed consent, confidentiality, voluntary participation, and academic integrity were strictly observed. Findings: Findings revealed that training opportunities significantly influence employees’ career development by enhancing professional skills, clarifying career goals, and improving competencies needed for advancement. The research contributes to the broader public sector HRM literature by highlighting how structured training can act as a key driver of career progression in local government contexts. Implications & Recommendations: The study recommends that Moshi Municipal Council adopt regular, inclusive, and need-based training programs aligned with both employee aspirations and organizational objectives. Contribution & Value Added: This research enriches scholarly debate by extending Herzberg’s Motivation-Hygiene Theory into a decentralized governance context, demonstrating that training functions as both a motivator and mechanism to address structural barriers in career growth.